Analisis Komparatif atas Hasil Tracer Study Program Studi Hubungan Internasional dan Administrasi Negara - Muhyar Fanani; Akhriyadi Sofian; Kaisar Atmaja; Endang Supriadi (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
One of the indicators of a developed faculty is the numbers of department organized by the faculty. In order to develop the faculty, the Faculty of Social and Political Sciences, the State Islamic University Walisongo had planned to prepare a new department. Applying the method of survey as a preliminary study, this research was purposed as tracer study. The research questions are those related to job acceptance of the alumni and how long the alumni to get job after they finish their study, it was revealed that the Department of International Relations and the Department of Public Administration have been assumed to be priorities. This study focused on six famous and highest rank state universities in Java having mentioned departments. Based on this research result, it was recommended to heads of the State Islamic University Walisongo to set up the Department of International Relations and the Department of Public Administration as the effort for developing the Faculty of Social and Political Sciences.